Facilitated c-Fos induction in mice deficient for the AMPA receptor-associated protein Ckamp44 - Yang, Boyi; Gass, Peter; Inta, Dragos (Cellular and molecular neurobiology, 2016)
The recently identified Cystine-knot containing AMPAR-associated protein (Ckamp44) represents a novel AMPAR-related protein that critically controls AMPAR-mediated currents and short-term plasticity. However, the effects of the lack of this protein at network level are not entirely understood. Here we used c-Fos brain mapping to analyse whether the excitatory/inhibitory balance is altered in the absence of the Ckamp44. We found that Ckamp44−/− mice treated with an NMDAR antagonist exhibited a very robust c-Fos expression pattern, similar with that seen in mice lacking the GluN2A subunit of NMDAR treated with the same compound. This finding is unexpected, in particular, since Ckamp44 expression is strongest in dentate gyrus granule cells and less abundant in the rest of the brain.
Gesehen am 25.06.2019
Published online: 8 December 2015